Optimizing Employee Performance: The Impact of Islamic Values, Skills, and Motivation in DPMPTSP Padang - Agusfina Fernata, Nadya; Mardani, Agnes Dini (Takaza Innovatix Labs Ltd., 2023)
This research investigates how Islamic values, skills, and motivation affect employee performance. The motivation behind this study stems from issues like the inadequate application of Islamic values, employee negligence, and a lack of self-motivation in the workplace. The focus is on the employees of the Investment and Integrated One-Stop Service Agency (DPMPTSP) in Padang City. Using a quantitative approach, the study involves all 55 employees at DPMPTSP Padang City, using the saturation sampling technique and SPSS for data analysis. The findings are as follows: Islamic values (X1) don't significantly impact employee performance due to limited integration into the organizational culture. Skills (X2), on the other hand, significantly improve performance by maintaining consistent skills through training. Work motivation (X3) also significantly boosts performance by offering equal growth opportunities to all employees. This research provides insights into what influences employee performance at DPMPTSP Padang City, highlighting the importance of work capability and motivation while suggesting ways to enhance Islamic values integration in the organization.